Clinical Practice Guidelines for delivery of healthcare to patients with Pompe disease - S. S. Nikitin; S. I. Kutsev; E. N. Basargina; S. V. Mikhaylova; E. Yu. Zakharova; V. I. Larionova; S. I. Polyakova; N. P. Kotlukova; E. N. Arkhipova; M. O. Kovalchuk; N. V. Buchinskaya (Нервно-мышечные болезни, 2016)
.